Nontemplate Synthesis of CH3NH3PbBr3 Perovskite Nanoparticles - Schmidt, Luciana Carina (2014)
To date, there is no example in the literature of free, nanometer-sized, organolead halide CH3NH3PbBr3 perovskites. We report here the preparation of 6 nm-sized nanoparticles of this type by a simple and fast method based on the use of an ammonium bromide with a medium-sized chain that keeps the nanoparticles dispersed in a wide range of organic solvents. These nanoparticles can be maintained stable in the solid state as well as in concentrated solutions for more than three months, without requiring a mesoporous material. This makes it possible to prepare homogeneous thin films of these nanoparticles by spin-coating on a quartz substrate. Both the colloidal solution and the thin film emit light within a narrow bandwidth of the visible spectrum and with a high quantum yield (ca. 20%); this could be advantageous in the design of optoelectronic devices.